INVESTOR'S SENTIMENT AGAINST THE LEGISLATION OF THE LAW ON RELOCATING THE STATE CAPITAL (STUDY ON A STATE-OWNED CONSTRUCTION COMPANY) - kharisma, Gilang (Fakultas Ekonomika dan Bisnis Universitas Selamat Sri, 2022)
This study aims to examine the effect of the announcement of the relocation of the new capital on government-owned construction companies. The first hypothesis is that there is a significant abnormal return on the day around the enactment of the law the relocation of the new capital by the DPR (People's Representative Council) and the second hypothesis is that there are differences in abnormal returns before and after the DPR passed the law on moving the country's capital. This study uses an event study research method, with the determination of t = 0 days in which the law on the relocation of the State Capital was passed, namely on January 18, 2022. Using secondary data obtained from yahoo finance. The state-owned construction company was chosen as the research sample because it is suspected to be directly related to the event being studied. The results of the study revealed that there was a positive reaction to the sample of companies in this study after the ratification of the law on moving the state capital, but no significant AAR value was found on the day around the ratification of the law on moving the state capital. Meanwhile, there was a significant difference in abnormal returns before and after the ratification of the law on moving the country's capital by the DPR as a reflection that the market had adequately responded to the event.